PENGEMBANGAN PROGRAM BIMBINGAN DAN KONSELING DALAM MEREDUKSI PERILAKU DISRUPTIVE SISWA KELAS 8 SEKOLAH MENENGAH PERTAMA - Dwika Sukma Dewi; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research aims to develop guidance and counseling programs in reducing disruptive behavior of students in class VIII SMP Negeri 4 Cimahi City. This is based on initial findings on the results of a need assessment using the Developmental Assignment Inventory which shows aspects of emotional maturity are still low, where students who have low emotional maturity tend to behave disruptive or disrupt the class. The research method used is Research & Development. The main objective of this research is to produce a product for developing a guidance and counseling service program at SMP Negeri 4 Cimahi.